DUOGLOBE: One‐Year Outcomes in a Real‐World Study of Levodopa Carbidopa Intestinal Gel for Parkinson's Disease. Issue 7 (12th September 2021) - Standaert, David G.; Aldred, Jason; Anca‐Herschkovitsch, Marieta; Bourgeois, Paul; Cubo, Esther; Davis, Thomas L.; Iansek, Robert; Kovács, Norbert; Pontieri, Francesco E.; Siddiqui, Mustafa S.; Simu, Mihaela; Bergmann, Lars; et al.
ABSTRACT: Background: Levodopa‐carbidopa intestinal gel (LCIG) is an established treatment for improving motor and some non‐motor symptoms (NMS) in patients with advanced Parkinson's disease (PD). Prospective long‐term data in routine clinical practice are limited. Objective: Assess LCIG effectiveness and safety in patients with advanced PD after 12 months during real‐world routine clinical practice. Methods: Duodopa/Duopa in patients with advanced Parkinson's disease—a global observational study evaluating long‐term effectiveness (DUOGLOBE) (NCT02611713) is an ongoing, prospective, multinational, observational study of LCIG‐naïve patients treated as part of routine clinical practice; 3 years of follow‐up are planned. The primary outcome is the change in patient‐reported off time. Other assessments include the Unified Dyskinesia Rating Scale (UDysRS), Non‐Motor Symptoms Scale (NMSS), Parkinson's Disease Sleep scale (PDSS‐2), Epworth Sleepiness Scale (ESS), health‐related quality of life (HR‐QoL), caregiver burden, and serious adverse events (SAEs). Outcomes from baseline to month (M) 12 are presented. Results: In this 12‐month follow‐up, patients (N = 195) had baseline characteristics similar to other LCIG studies. Significant improvements (mean change to M12) were observed in off time (−3.9 ± 3.6 hr/day, P  < 0.001), dyskinesia assessed using the UDysRS (−9.6 ± 22.5, P  < 0.001), NMSS (−23.1 ± 41.4, P  < 0.001), sleep and sleepiness symptoms on the PDSS‐2 (−6.5 ± 12.2, P  < 0.001) and ESS (−1.0 ± 5.7, P  < 0.05), HR‐QoL (−9.0 ± 21.6, P  < 0.001), and caregiver burden (−1.9 ± 6.7, P  = 0.008). Overall, 40.5% (n = 79) of patients experienced SAEs; fall (n = 6; 3.1%) and urinary tract infection (n = 6; 3.1%) were SAEs reported in ≥3% of patients. Conclusions: These 12‐month outcome data show sustained, long‐term improvements and support the real‐world effectiveness of LCIG in patients with advanced PD. Safety was consistent with previous studies.